2014
DOI: 10.1016/j.jss.2014.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Standardized and quality-assured video-recorded examination in undergraduate education: informed consent prior to surgery

Abstract: The VOSCE is both feasible and reliable as a method of assessing student communication skills and the application of clinical knowledge while obtaining informed consent in surgery. This method is efficient (flexible rating outside normal working hours possible with reductions in administrative load) and may be used for high-stakes evaluation of student performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 22 publications
1
20
0
6
Order By: Relevance
“…The calculated ICC values considering all raters indicated that there were variations in scoring. It should be noted that although we consider our ICCs as moderate, discrepancies exist across studies for ICC interpretation [5,13,25,26,27,28]. Consistent with our findings, the literature has shown interrater reliability between video and direct scoring to be moderate or higher [3,13,18].…”
Section: Discussionsupporting
confidence: 85%
“…The calculated ICC values considering all raters indicated that there were variations in scoring. It should be noted that although we consider our ICCs as moderate, discrepancies exist across studies for ICC interpretation [5,13,25,26,27,28]. Consistent with our findings, the literature has shown interrater reliability between video and direct scoring to be moderate or higher [3,13,18].…”
Section: Discussionsupporting
confidence: 85%
“…Two independent and “blinded” evaluators (a senior medical student and a physician in internship who used this analysis as his doctoral thesis) were recruited and extensively trained individually and as a group, and repeatedly supervised by a multidisciplinary expert panel to rate the videotaped performances [17] using a rating check list. Evaluators were provided with a detailed evaluator’s manual based on criteria of an expert panel of medical practitioners and smoking researchers used in Swiss smoking cessation courses, including a questionnaire assessing whether the student, in the role of a counsellor, covers the most important points of smoking cessation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, oral test parts are video-recorded in the SAM-test. This method of testing and performance evaluation, called VOSCE (Video-Recorded Objective Structured Clinical Examination), has successfully proven to be a feasible, reliable and valid method to assess communication ability in other medical contexts [21], [22], [23]. Since storing and accessing recorded test data can be problematic in view of strict data protection and privacy laws, a special software program was developed.…”
Section: Project Description and Methodologymentioning
confidence: 99%